Subordination in contracts for the provision of services (2019)
The contracting for the provision of services is frequently used by the entities of the Colombian state to replace payroll employees, this modality is direct contracting and has been used to link natural persons on a temporary basis in order to meet specific obligations to meet a need of general interest. The service contractor executes the tasks with its own autonomy but in turn is confused with a labor contract or reality. It is necessary for the state to establish clear and precise guidelines on this modality, since it is only limited to giving its definition and warning that it does not generate an employment relationship, additionally the same entities should respect and comply with them; being these those that impose this modality of work to avoid the payment of the labor rights (stable employment, social benefits) to the contractor who in turn carries out own activities of plant personnel.